The Decision to Use Halal Cosmetics: Influence of Quality, Benefits, Awareness, and Brand Image - Ayu Wandirah; Fahrul Hudatil Atkiyan; Andri Juansha; Jeihan Ali Azhar (Journal of Islamic Economic Laws, 2024)
The purpose of this research is to ascertain the influence of brand image-mediated product quality, product benefits, and awareness on travelers' decisions to use halal cosmetics while in Lombok, West Nusa Tenggara. This research is a quantitative study using primary data obtained from distributing questionnaires. A total of 305 respondents who have visited Lombok, NTB, made up the study's sample. The technique for data analysis is Structural Equation Modeling based on Partial Least Squares or SEM-PLS. It is known that product quality has no bearing on whether or not someone chooses to use halal cosmetics based on data analysis findings. The decision of Lombok NTB tourists to use halal cosmetics is, however, influenced positively by the benefits of the product, awareness, and brand image. Meanwhile, brand image is unable to mediate the relationship between product quality, benefits, and awareness of the choice to use halal cosmetics among Lombok NTB tourism.